Demographic Changes on the Habsburg-Ottoman Border in Slavonia (c. 1570-1640) - Štefanec, Nataša (Array, 2005)
The paper offered an initial demographic analysis of the two data-bases containing information from several types of extensive military conscriptions that allowed statistical elaboration. First, comparatively scrutinising the data dating from the 1570s to the 1640s, the authoress reconstructed the grid of fortresses on the Habsburg and Ottoman side of the border, in several maps. Second, she analysed the salaries of border officials and soldiers. Third, based on the examination of names and surnames, she presented the distribution of the autochthonous people among the army units and fortresses as well as the infiltration of newcomers from various historical lands (Inner-Austria to Herzegovina) into the paid troops and fortresses on the Habsburg side of the Military Border. Fourth, aided by the studies in dialectology, the authoress portrayed the results of these migrations from the Ottoman Croatia and Slavonia, as well as from deeper Balkan interior, to the Slavonian Border.